Sikap Sopan Santun yang Harus Dimiliki Mahasiswa - Yolanda Br. Tarigan; Leoni Putri Cantika Hulu; Reza Sahputra Sihombing (Yayasan Literasi Sains Indonesia, 2024)
Manners are a determinant of the quality of a teenager's personality. Because everyone can be smart, but not everyone has good manners within themselves. What's more, as the times progress, politeness in teenagers is decreasing, where this is mostly caused by promiscuity . The results of research conducted at STIKes Santa Elisabeth Medan used a descriptive design with a quantitative approach. Descriptive research is used to analyze data by describing or describing the data that has been collected as it is without the intention of making general conclusions or generalizations. Results are the main part of a scientific article, containing: clean results without data analysis process, hypothesis testing results. The objectives of the discussion are: Answering research problems, interpreting findings, integrating findings from research into existing bodies of knowledge and developing new theories or modifying existing theories. Suggestions that can be given by researchers to students, especially health information management students, are to continue to maintain an attitude which according to the research results is quite good and try to continue to improve polite behavior not only in the lecture environment but wherever they are and also avoid all impolite behavior, and for lecturers to give firmer warnings to students who break the rules or who behave impolitely so that students pay more attention to politeness or can also give rewards or praise to students who behave well so that students feel happy if they have behave well SPEECH.